Investigation of agreement between wastewater-based epidemiology and survey data on alcohol and nicotine use in a community. (1st May 2016) - van Wel, J.H.P.; Gracia-Lor, E.; van Nuijs, A.L.N.; Kinyua, J.; Salvatore, S.; Castiglioni, S.; Bramness, J.G.; Covaci, A.; Van Hal, G.
Highlights: Weekly trends in alcohol and nicotine use can be quickly detected from wastewater analysis. Large regional events can be picked up retrospectively in wastewater data. Meaningful correlations between survey and wastewater results were difficult since the number of survey responses was very low. Abstract: Background/aims: Alcohol and nicotine are the two most used substances world-wide and associated with increased burden of disease. Since surveys on substance use may be difficult due to response biases, wastewater-based epidemiology (WBE) was developed as a more objective measure of nicotine and alcohol use. This study compares estimates of nicotine and alcohol use from a wastewater sampling campaign in a medium-sized Belgian city with a concurrently executed population survey. Methods: 29, 083 letters about participation in an online survey study on weekly alcohol and tobacco use were sent to the inhabitants of Lier, Belgium. Wastewater samples were collected from the associated treatment plant in four bi-weekly periods. Samples were analyzed using liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS). Ethylsulfate was used as alcohol biomarker and cotinine and trans -3′-hydroxycotinine as nicotine biomarker. Results: 263 (1%) surveys were filled out on average per week. According to survey data, alcohol and nicotine were used less than in the rest of Belgium and this was matched by the wastewater data. Nicotine use, but not alcohol use, showed a significant variation over the sampling periods. Both nicotine and alcohol showed increase use during the weekend while only alcohol showed a different use pattern throughout the week. Conclusion: No correlation between WBE and survey data could be demonstrated, possibly due to small sample sizes. However, this study shows that weekly trends in alcohol and nicotine use can be quickly detected from wastewater analysis and the occurrence of major events such as festivals can be identified.